“so much about myself I didn’t understand”: rememory and the problematics of a lost identity in Sally Morgan’s My Place - Raihanah M.M.; Mohd Muzhafar Idrus (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper presents the problems of a lost identity in My Place, an Australian aboriginal autobiography by Sally Morgan. Albeit literary critics have questioned the 'indigeneity' and 'reality' concerning the narration of stolen generation, this paper situates the reading of My Place within the issue of (un)making and recuperation of socio cultural consciousness of the self. Through the lens of rememory as an exercise of recollection and rediscovery of the past, the analysis focuses on the triangulation of the themes of self, culture, and consciousness as represented in My Place. The findings indicate that rememory as illustrated in My Place, is evident in the protagonist's exploration of her personal history, her discovery of cultural/racial history, and her realisation of the double consciousness that comes with being a member of the aboriginal community.